Ethnography and An Ethnography in the Human Conversation - Wardle, Huon; Gay y Blasco, Paloma (Anthropologica, 2022)
What transforms the process of ethnography endow- ing it with its thing-like, modal character as an ethnography? This article examines how ethnography becomes an ethnogra- phy on the one hand, through the manipulation of descriptive and analytical diversity and, on the other, by way of the ambiguation (and disambiguation) of authorial agency The purification of ethnography as an ethnography mimics some of the effects of the scientific laboratory while introducing new complications.